Finite element simulation of cylindrical liquid storage tank under tri-directional components of earthquake - Rawat, Aruna; Matsagar, Vasant; Nagpal, A.K. (Journal of Structural Engineering, 2025)
Seismic response of ground-supported, three-dimensional (3-D) cylindrical liquid storage tank subjected to tri-directional components of earthquake ground motion is investigated, using coupled acoustic-structural finite element (FE) method. The FE modeling of the interaction is carried out in Abaqus® software. In this method, the tank wall is modeled using shell elements and contained liquid in the tank using acoustic elements. The acoustic elements are based on linear potential theory having single pressure degree-of-freedom at each node. A parametric study is conducted for broad and slender tanks subjected to tri-directional components of five different earthquake ground motions. The time history responses of sloshing displacement and base shear are obtained, and compared with the bi-directional horizontal components of the earthquake ground motions. Based on the computed results, it is observed that sloshing displacement and base shear increases under the tri-directional components of earthquake ground motion. Also, hydrodynamic pressure distribution increases due to the tri-directional components of earthquake.